2021
DOI: 10.1093/jhered/esaa059
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Connectivity in Plant Species Differing in Clonality and Dispersal Mechanisms in Wetland Island Habitats

Abstract: In plants, long-distance dispersal is both attenuated and directed by specific movement vectors, including animals, wind, and/or water. Hence, movement vectors partly shape metapopulation genetic patterns that are, however, also influenced by other life-history traits such as clonal growth. We studied the relationship between area, isolation, plant-species richness, reproduction, and dispersal mechanisms with genetic diversity and divergence in 4 widespread wetland plant-species in a total of 20 island-like ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 87 publications
0
12
1
Order By: Relevance
“…Moreover, Nm estimates were significantly higher among populations belonging to each of the two genetic clusters ( Nm = 1.295 for HN group, Nm = 0.961 for IC group) than the mean for the species as a whole, suggesting greater gene flow at the scale of either landmass. Similarly, whilst our Fst estimate for P. pulcherrima is somewhat higher than the mean calculated for the orchid family as a whole (0.146; Philips et al., 2012 ), it is considerably lower than for many other terrestrial habitat island specialists (e.g., Pinheiro et al., 2014 ; Gao et al., 2015 ; Nistelberger et al., 2015 ; Lexer et al., 2016 ; Wanderley et al., 2018 ; Lozada-Gobilard et al., 2021 ), suggesting that the species is comparatively mobile in the context of habitat specificity.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Moreover, Nm estimates were significantly higher among populations belonging to each of the two genetic clusters ( Nm = 1.295 for HN group, Nm = 0.961 for IC group) than the mean for the species as a whole, suggesting greater gene flow at the scale of either landmass. Similarly, whilst our Fst estimate for P. pulcherrima is somewhat higher than the mean calculated for the orchid family as a whole (0.146; Philips et al., 2012 ), it is considerably lower than for many other terrestrial habitat island specialists (e.g., Pinheiro et al., 2014 ; Gao et al., 2015 ; Nistelberger et al., 2015 ; Lexer et al., 2016 ; Wanderley et al., 2018 ; Lozada-Gobilard et al., 2021 ), suggesting that the species is comparatively mobile in the context of habitat specificity.…”
Section: Discussioncontrasting
confidence: 85%
“…Unifying these taxonomically disparate plants, and underlying their ecological specialisation, are a number of functional traits, including a variable combination of pollinator specificity, self-compatibility, a tendency towards selfing, frequent inbreeding among related individuals and/or short-range seed dispersal. In fact, these traits have been identified in a number of plants restricted to a variety of terrestrial island-like systems, and in some cases they have been linked to clonality and low reproductive success, too ( Lhuillier et al., 2006 ; Lozada-Gobilard et al., 2021 ). Combined with high habitat specificity, these attributes can render habitat island species prone to fixation and drift ( Pinheiro et al., 2014 ; Nistelberger et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only a handful of studies have genotyped both haploid and diploid stages, Krueger-Hadfield et al (2021) found that available empirical data broadly support the theoretical predictions proposed by Stoeckel et al (2021). Lozada-Gobilard et al (2021) consider the importance of both reproductive mode (clonal versus nonclonal) and dispersal mechanism for shaping plant metacommunities occurring in island-like kettle-hole habitats. Ryan et al (2021) offers an intriguing look at how reproductive plasticity, in the form of temperature-dependent fission, may help shape the historical distribution of clones and genetic diversity in the non-native range of an invasive sea anemone.…”
Section: The Symposiummentioning
confidence: 87%
“…The effect of patch size on local genetic diversity was negligible or even negative. This may be due to increased inter-speci c competition as the emergence of more competitive species in late successional stages may suppress seedling recruitment in O. aquatica, a process likely more pronounced in larger patches(Schöpke et al, 2019;Lozada-Gobilard et al, 2021) ultimately resulting in ephemeral population built-up. Hence, unlike in populations that are resulting from progressive fragmentation of continuous habitat, the extent of genetic variation and connectivity in our study system is less a matter of patch size(Plue et al, 2017) than a matter of small-scale environmental conditions and historical population establishment in the naturally scattered landscape.…”
mentioning
confidence: 99%